A Note on the Possibility of Decentralization in a Model of Allocation of Resources - Maiti, Pradip; Sengupta, Ramprasad (Management Science, 1973)
The decomposition algorithm for the solution of large-scale linear programmes has been interpreted by Baumol and Fabian (Management Science, September, 1964) as a procedure for decentralized decision by the multi-division company or the multi-sector economy. While commenting on the possibility of decentralization in this context, they maintain that an economy's optimum point will not in general yield a sectoral optimum. The present note demonstrates that this contention is not valid.